Encounter between second-career teachers and their school: A marriage without romance - Coppe, Thibault; März, Virginie; Raemdonck, Isabel (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2022)
This contribution documents the professional integration of novice second-career teachers working in technical and vocational schools. We studied the experiences of this particular population of teachers through a qualitative study design with seven participants. The results highlight the harshness, difficulty, and complexity of this process. They experience institutional, organizational, and individual difficulties. In particular, the familiarization with the school as a new workplace is experienced as a complex process. The conclusions of the study provide insights on the consequences of the legal framework regulating access for second-career teachers to the teaching profession and the necessary training and support for these kinds of teachers.